Evaluating efficiency of zakat institution in Kedah state using two-stage network data envelopment analysis - Muhammad Aiman, Mohd Azhary (2024)
Zakat institutions are trusted bodies that manage and administer matters related to zakat affairs in most Muslim countries. However, issues regarding inefficiency in the distribution of zakat collection in Malaysia have been continuously raised by the public. Therefore, this study measures the efficiency of zakat collection, zakat distribution and overall zakat efficiency in Lembaga Zakat Negeri Kedah (LZNK) by using a two-stage network Data Envelopment Analysis (DEA) model. The model was applied to measure the efficiency of LZNK from 2018 to 2020, assigning each regional zakat center (PZD) in Kedah as the decision-making units (DMU). In the two-stage network DEA model, the first stage provides the efficiency of zakat collection, while the second stage measures the efficiency of zakat distribution and also the overall zakat efficiency. In the first stage, four input variables were considered which are zakat staff, zakat payers, zakat expenses and total population while one output included which is total zakat collected. In the second stage, the output was considered as the intermediate input variable, while total zakat distributed was considered as the output. DMUs are considered efficient if both stages are efficient, with an efficiency score of one. The results obtained from the analysis shows that none of the DMUs are efficient since no DMU achieve the efficiency score of one for both stages. Thus, the overall zakat efficiency during those years is relatively inefficient. This study can identify which PZD are inefficient in each stage and provides new ideas to improve their performance in zakat management and operation.